2024
DOI: 10.1021/acsabm.4c00114
|View full text |Cite
|
Sign up to set email alerts
|

Porous Membrane Electrical Cell–Substrate Impedance Spectroscopy for Versatile Assessment of Biological Barriers In Vitro

Oleg Chebotarev,
Alisa Ugodnikov,
Craig A. Simmons

Abstract: Cell culture models of endothelial and epithelial barriers typically use porous membrane inserts (e.g., Transwell inserts) as a permeable substrate on which barrier cells are grown, often in coculture with other cell types on the opposite side of the membrane. Current methods to characterize barrier function in porous membrane inserts can disrupt the barrier or provide bulk measurements that cannot isolate barrier cell resistance alone. Electrical cell–substrate impedance sensing (ECIS) addresses these limitat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Implementation of ECIS electrodes on porous membrane cell culture inserts has recently been performed by Rajasekaran et al 237 and by Chebotarev et al 247,248 The latter studies introduced a novel, cost-effective fabrication method for integrating gold electrodes onto porous membrane in Transwell-like inserts, enabling sensitive detection of barrier formation and disruption, as well as simultaneous validation against conventional TEER and molecular permeability in the same devices. 247,248 This electrode configuration lends itself well to OOC barrier modes, facilitating direct measurements of monolayers in complex OOC systems that contain multiple cell types, as demonstrated in models of the placenta 74 and BBB 73 (Fig. 5F).…”
Section: Methods For Barrier Integrity Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of ECIS electrodes on porous membrane cell culture inserts has recently been performed by Rajasekaran et al 237 and by Chebotarev et al 247,248 The latter studies introduced a novel, cost-effective fabrication method for integrating gold electrodes onto porous membrane in Transwell-like inserts, enabling sensitive detection of barrier formation and disruption, as well as simultaneous validation against conventional TEER and molecular permeability in the same devices. 247,248 This electrode configuration lends itself well to OOC barrier modes, facilitating direct measurements of monolayers in complex OOC systems that contain multiple cell types, as demonstrated in models of the placenta 74 and BBB 73 (Fig. 5F).…”
Section: Methods For Barrier Integrity Assessmentmentioning
confidence: 99%
“…270 Similarly, heat-bonded gold leaf provides a flat, continuous electrode surface with lower resistivity compared to sputtered gold. 247 Interestingly, inkjet-printed gold electrodes can have as much as 10-fold greater sensitivity compared to sputtered gold. 258 Meanwhile, the surface morphology – and therefore sensitivity – of nanoporous gold may vary depending on fabrication method ( e.g.…”
Section: Challenges For Barrier Integrity Assessment In Oocmentioning
confidence: 99%
“…Each insert comprised gold electrodes patterned onto a porous transparent PETE membrane filter (3.0 μm, 6 × 10 5 pores/cm 2 ; Sterlitech, 1300032) on which endothelial cells were cultured. Device fabrication was performed based on published protocols . Briefly, this process involves thermal bonding of gold leaf (Gold Leaf Supplies, 2300/RUXX) to the membrane, followed by UV lithography to pattern the electrodes and laser cutting of the electrode-patterned membrane to size and shape for mounting in the custom insert (Figure A).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, this process involves thermal bonding of gold leaf (Gold Leaf Supplies, 2300/RUXX) to the membrane, followed by UV lithography to pattern the electrodes and laser cutting of the electrode-patterned membrane to size and shape for mounting in the custom insert (Figure A). We previously showed that heat-bonded gold leaf PM-ECIS electrodes have more uniform coverage and thickness than electrodes etched on sputter-coated membranes, resulting in similar variance but lower overall resistivity vs sputtered electrodes …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation